(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
Not available. Keywords: Actinodaphne; Critically Endangered; Lauraceae; Lectotype; Southern Western Ghats. Bangladesh J. Plant Taxon. 24(1): 119123, 2017 (June)